The Influence of Availability of Muslim Friendly Facilities towards Indonesian Muslim Tourist Revisit Intention to Japan - Hariani, Dina; Rahmanita, Myrza; Ingkadijaya, Rahmat (Institut Pariwisata Trisakti, 2017)
As the market of halal tourism destinations has increasingly become more competitive, the revisit intention topic has progressively become prominent to emphasize on. This research is designed to find out how much influence of the availability of Muslim-friendly facilities to Indonesian Muslim tourist to revisit intention to Japan. The methodology of this research is quantitative descriptive research in which questionnaire is the major tool in collected the primary data for analysis. The total sample of 100 Indonesian Muslim tourist is obtained for the analysis. The simple and multiple regression analysis are adopted to examine the key factors which significantly predict the revisit intention. The results of this research indicates that Muslim-friendly facilities likes halal hotel, halal restaurant, and prayer room are positively related to the revisit intention. The biggest need of Indonesian Muslim tourist is the availabity of halal restaurants. Regarding the situation of Muslim friendly facilities in Japan, Indonesian Muslim still finds it difficult to locate the facilities despite its availability.